2019
DOI: 10.1186/s40623-019-1061-3
|View full text |Cite
|
Sign up to set email alerts
|

Rupture processes and Coulomb stress changes of the 2017 Mw 6.5 Jiuzhaigou and 2013 Mw 6.6 Lushan earthquakes

Abstract: Since the 2008 great M w 7.9 Wenchuan earthquake, two destructive earthquakes, the 2013 M w 6.6 Lushan earthquake and the 2017 M w 6.5 Jiuzhaigou earthquake, struck the eastern margin of the Tibetan Plateau, causing many casualties and significant property damage. The rupture processes and Coulomb stress change of the Lushan and Jiuzhaigou earthquakes are investigated in this study. The general patterns of the slip models of the two events are similar, where the slip is concentrated around the hypocenter and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 88 publications
3
11
0
Order By: Relevance
“…We depict the stress changes on nearby active faults caused by the Wenchuan and Lushan earthquakes in Figure 10. Following the Lushan earthquake, the CFS increased on the PGF and BYF by nearly 0.1 bar and 0.2 bar, respectively, which agree well with the results of Lin et al [24]; it is possible that this stress change will result in future earthquakes. Following the Wenchuan earthquake, the CFS increased on the following faults (as shown in Figure 10a): the middle part of the XSHF, the WQF, the LRBF, the BYF and the southern segment of the PGF.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We depict the stress changes on nearby active faults caused by the Wenchuan and Lushan earthquakes in Figure 10. Following the Lushan earthquake, the CFS increased on the PGF and BYF by nearly 0.1 bar and 0.2 bar, respectively, which agree well with the results of Lin et al [24]; it is possible that this stress change will result in future earthquakes. Following the Wenchuan earthquake, the CFS increased on the following faults (as shown in Figure 10a): the middle part of the XSHF, the WQF, the LRBF, the BYF and the southern segment of the PGF.…”
Section: Discussionsupporting
confidence: 90%
“…Our results demonstrate that the Wenchuan earthquake increased the CFS by up to 0.2 bar at the hypocenter of the Lushan earthquake, which exceeded the threshold value (0.1 bar) of earthquake triggering [58]. Lin et al [24] found that the Wenchuan earthquake had a significant impact on the surrounding area and verified that the Lushan earthquake was probably promoted (possibly triggered) by the 2008 Wenchuan earthquake. There were few aftershocks or smaller events about Mw 6 that occurred in this area between the 2008 Wenchuan and 2013 Lushan events.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations